10.1016/s0967-0653(95)97469-5 (CrossRef Listing of Deleted DOIs, 2000)
BACKGROUND: Preoperative anxiety is common among women undergoing breast cancer surgery and is associated with impaired subjective well-being as well as adverse perioperative outcomes, including increased postoperative pain, nausea and vomiting, and higher analgesic requirements. While preliminary evidence suggests potential benefits of nonpharmacological interventions, including acupuncture, robust clinical evaluation of safe and feasible approaches in perioperative oncology is still needed. The National Acupuncture Detoxification Association (NADA) protocol, a standardized 5-point auricular approach, has been investigated for its potential stress-regulating effects in other clinical contexts but has not yet been systematically evaluated in perioperative breast cancer surgery. To the best of our knowledge, this is the first randomized controlled trial to evaluate whether NADA auricular acupressure, when added to standard preoperative care, reduces perioperative anxiety and pain in women with newly diagnosed breast cancer undergoing therapeutic surgery. OBJECTIVE: The present study aims to evaluate the effects of NADA auricular acupressure on perioperative anxiety and pain in patients with a first diagnosis of breast cancer undergoing therapeutic breast surgery. In addition, we will exploratorily assess whether this intervention further impacts decisions regarding the initiation or use of other complementary and integrative medicine (CIM) therapies within the first 3 months following surgery. METHODS: This prospective, 2-arm, parallel randomized controlled trial will enroll 66 women with newly diagnosed breast cancer undergoing therapeutic surgery. Participants will be randomized 1:1 to receive either NADA auricular acupressure in addition to standard preoperative care or standard preoperative care alone. The primary outcome is preoperative state anxiety measured prior to surgery (T1) using the State-Trait Anxiety Inventory-State. Secondary outcomes include postoperative anxiety, preoperative and postoperative pain, postoperative nausea and vomiting, analgesic and antiemetic medication use, and postoperative complications. The subsequent use of CIM at the 3-month follow-up will be an exploratory outcome. Analyses will follow the intention-to-treat principle using analysis of covariance, linear mixed-effects models, linear regression, and logistic regression as appropriate. RESULTS: Recruitment began in March 2026. At the time of manuscript submission, 8 participants have been recruited. The target sample size (N=66) is expected to be reached by April 2027, with data collection completed by July 2027 and results anticipated in September 2027. CONCLUSIONS: Conducted under routine clinical conditions, this trial evaluates NADA auricular acupressure within a real-world perioperative oncology setting. The randomized design and standardized intervention protocol represent key methodological strengths, while the absence of blinding and a sham control constitute important limitations. By addressing a relevant gap in the current evidence base on NADA auricular acupressure in perioperative oncology, this study will inform clinical practice and guide future research.